ІMPORTANCE SMS 'OBJECTIVELY INDICATORS DENTAL HEALTH FOR EVALUATION FACTORS RISK OF CARIES TEETH IN CHILDREN - E.V. Bezvushko; L.S. Lahoda (Ukrainian Medical Stomatological Academy, 2016)
Introduction Epidemiological studies indicate that the occurrence of caries in children of different age groups is 63.3% - 98.3%. It is of particular concern that the trend of increasing intensity of caries in children within key age groups - 12 years. Analysis of the preventive measures used in practice dentists indicated on mostly toiletries oral hygiene, fluoride-varnish, sylanty. However, very little attention is paid to risk factors of caries, the daily eating habits of children, awareness of oral care, motivation to regular dental visits and scheduled dental treatment. We know criterion proposed by WHO for dental health monitoring and the risk of dental diseases. Nowadays the most rational information system is EGOHID - 2005. The aim is to determine the significance of the subjective indicators for dental health evaluation to assess risk factors of dental caries in children. Material and methods. A dental examinations and anonymous follow of two children ages 12 and 15 years after 100 children. These dental results have made a map of the dental examination and questionnaires for WHO. An examination of the children registered CPV permanent teeth, oral hygiene index Green Vermilyona (OHI-S) and bleeding gums by WHO methodology. In an anonymous questionnaire modified by WHO in 2013 there were 11 issues, which included visits to the dentist, frequency of tooth brushing, use of fluoride toothpaste, drinking soda. In this publication were analyzes the 5 questions. Indicator B5 Results revealed that among the surveyed students 12 years of age only 25% visited the dentist once a year, and among 15-year - 34.2%. A significant percentage of students indicated that they did not go to the dentist. Among 12-year-old girls the figure was 20% and 13% of 15 year olds. Has been found a significantly higher percentage of boys 12 and 15 years of age, for years did not attend the dentist. Proof of the importance of the indicator is B5 D2 - the number of children experiencing dental pain. Revealed that in the last 12 months, a high percentage of children 12 years and 15 years of age (40% and 68.4% respectively) felt a toothache. It is proved that in case of unsatisfactory oral hygiene dental caries intensity rises. According to our data the largest percentage of the recommended treatment is to brush 2 times a day for 15 years boys - 60%. To use fluoride toothpaste is one of the most effective methods of local prevention of caries. According to gotten data fairly small percentage of children brush teeth with fluoride toothpaste (boys 12 - 15%, girls - 10%, students 15 years - 33% and 21.7% respectively). Most surveyed students did not know the toothpaste they use (65-85%). Daily consumption of sugary foods, beverages promotes the growth of dental plaque on the tooth surface, which in turn leads to the risk of dental caries. The survey results revealed that 52-58% of children consume sweets on a daily basis and 56.2% to 45% rare. Most often children eat candy, cookies 22,5-28,9%. Conclusions European indexes of dental health (EGOHID - 2005) can determine the risk factors for caries, as well as to monitor the dental health of children. Comparative evaluation of subjective and objective indicators of school-age children will help optimize prevention, effectiveness of preventive measures for the individual and mass levels.